(untitled) (Italian Review of Legal History, 2023)
The Statute of Florence of 1355, in both its Latin and vernacular versions, is a complex text, mirroring the city’s rich but complicate regulatory heritage. Two aspects appear evident and also seemingly contradictory. On the one hand, the strongly authoritarian approach: the Commune is very careful to regulate all aspects of social life, especially in the economic and judicial spheres. On the other, the great emphasis on citizen participation in public life, which is witnessed in the choice to translate the text into the vernacular, but it is clear also in the many rules on collegial municipal offices. The essay examines this apparent contradiction and suggests its solution in the role played by the Statute, as a point of reference for regulatory texts that had remained autonomous until the middle of the century.